Efficacy of two vaccines against recent emergent antigenic variants of clade 2.3.2.1a highly pathogenic avian influenza viruses in Bangladesh. Issue 21 (18th May 2021) - Kwon, Jung-Hoon; Criado, Miria Ferreira; Killmaster, Lindsay; Ali, Md Zulfekar; Giasuddin, Mohammad; Samad, Mohammed A.; Karim, Md Rezaul; Brum, Eric; Hasan, Md Zakiul; Lee, Dong-Hun; Spackman, Erica; Swayne, David E.
Highlights: Two licensed vaccines provided protection against H5N1 viruses from Bangladesh. Most H5N1 HPAIV from Bangladesh (2016–2018) had similar antigenicity. Cartographic analysis shows a house crow isolate as an antigenic outlier. Monitoring of HPAIV is crucial for early detection of vaccine resistant strains. Abstract: H5N1 highly pathogenic avian influenza viruses (HPAIVs) have caused outbreaks in poultry in Bangladesh since 2007. While clade 2.2.2 and 2.3.4.2 HPAIVs have not been detected since 2012, clade 2.3.2.1a viruses have caused continuous outbreaks since 2012 despite the use of vaccines. In this study, we evaluated the efficacy of two H5 vaccines licensed in Bangladesh, RE-6 inactivated vaccine, and a recombinant herpesvirus of turkeys vaccine with an H5 insert (rHVT-H5), for protection against recent field viruses in chickens. We selected three viruses for efficacy tests (A/chicken/Bangladesh/NRL-AI-3237/2017, A/crow/Bangladesh/NRL-AI-8471/2017 and A/chicken/Bangladesh/NRL-AI-8323/2017) from 36 H5 viruses isolated from Bangladesh between 2016 and 2018 by comparing the amino acid sequences at five antigenic sites (A-E) and analyzing hemagglutination inhibition (HI) titers with reference antisera. The RE-6 and rHVT-H5 vaccines both conferred 80–100% clinical protection (i.e. reduced morbidity and mortality) against the three challenge viruses with no significant differences in protection. In addition, both vaccines significantly decreased viral shedding from infected chickens as compared to challenge control chickens. Based on these metrics, the current licensed H5 vaccines protected chickens against the recent field viruses. However, the A/crow/Bangladesh/NRL-AI-8471/2017 virus exhibited antigenic divergence including: several unique amino acid changes in antigenic epitope sites A and B and was a serological outlier in cross HI tests as visualized on the antigenic map. The continuing emergence of such antigenic variants which could alter the dominant antigenicity of field viruses should be continuously monitored and vaccines should be updated if field efficacy declines.